IDO1 correlates with the immune landscape of head and neck squamous cell carcinoma: a study based on bioinformatics analyses - Gkountana, Georgia Vasiliki; Wang, Lezhou; Giacomini, Martina; Hyytiäinen, Aini; Juurikka, Krista; Salo, Tuula; Al-Samadi, Ahmed (Frontiers in Oral Health, 2024)
Background: Head and neck squamous cell carcinoma (HNSCCs) is a common cancer type with a high mortality rate and poor prognosis. Recent studies have focused on the role of immune checkpoints in HNSCC progression and in their potential use as prognostic markers and immunotherapeutic candidates. Some immune checkpoints, such as PD-1 and PD-L1, have been studied thoroughly in HNSCC. Other molecules, such as indoleamine 2,3-dioxygenase 1 (IDO1), have been investigated minimally.Methods: IDO1 expression, prognostic potential, and association with the immune profile of HNSCC were explored using online databases, including GEPIA, UALCAN, TIMER2.0, cBioPortal, and LinkedOmics, which utilize TCGA datasets and are freely available for use. For validation purposes, seven pairs of primary and metastatic HNSCC were immunostained for IDO1.Results: Our analysis revealed significantly higher expression of IDO1 in HNSCC, especially in HPV+ SCCs compared with healthy control tissue. However, IDO1 expression showed weak to no prognostic potential for overall and disease-free survival in HNSCC. IDO1 expression in HNSCC was positively correlated with several immune-related molecules, including most of the immune checkpoints. Additionally, GO enrichment analysis revealed that several immune-related pathways are positively correlated with IDO1 expression in HNSCC, such as response to type I interferon and lymphocytemediated immunity pathways. Finally, IDO1 expression positively correlated with infiltration of most of the immune cells in HNSCC, such as CD4+ T cells, CD8+ T cells, M1 and M2 macrophages, dendritic cells, and B cells.Conclusion: IDO1 expression is closely correlated with the immune profile of the HNSCC. This observation should be explored further to elucidate the potential of targeting IDO1 as a novel immunotherapeutic approach for HNSCC. Table 2: Correlation analysis between IDO1 expression levels and drug sensitivity on HNSCC cell lines. Green lines represent positive and red lines negative correlated drugs. GDSC Drug Target(s) IDO1 Correlation (Spearman Rho) GDSC pvalue Clinical Trial for Cancers Clinical Trial for HNSCC MG-132 Proteasome 0.9 0.03739 No No Z-LLNIe-CHO γ-secretase 0.9 0.03739 No No AZD6482 (KIN-193) PI3Kβ (P3C2B) -0.297 0.00546 No No UNC1215 L3MBTL3 -0.416 0.0069 No No BX-912 PDK1 (PDPK1) -0.388 0.01122 No No OSI-930 KIT, VEGFR, PDGFR -0.363 0.01816 Yes No CAL-101 (idelalisib)